Employees’ willingness to adopt a foreign functional language in multilingual organizations: The role of linguistic identity - Bordia, Sarbari; Bordia, Prashant (Journal of International Business Studies, 2015)
Language holds a central role in sustainable international expansion for multinationals. The choice of the functional language can facilitate or hinder communication between headquarters and subsidiary locations. In order to communicate effectively with the parent organization, host country employees often have to adopt a language that is not native to the subsidiary region. We take a subsidiary employee perspective in presenting an interdisciplinary theoretical model of host country employees’ willingness to adopt a foreign language in multinational organizations. The construct of linguistic identity, shaped by the linguistic landscape of the host location, is introduced as an important determinant in this process. Specifically, the foreign functional language may pose a threat to the employees’ existing linguistic identity; willingness to adopt the foreign functional language may depend upon the extent of this perceived threat. We incorporate the effects of foreign language proficiency and individuals’ motivation for enhancement in the theoretical model. Both high proficiency in a foreign language and need for social, economic, and career enhancements can increase individuals’ willingness to adopt the foreign functional language. Finally, we develop and present implications of the linguistic identity processes for entry mode, location, and language strategies.